Study of the Academic Culture of Religion-Based Schools in Urban Areas - Rosikin, Rosikin; Gozali , Imam; Fatimah, Siti; Siswanto, Achmad; Riady, Yasir (International Journal of Business, Law, and Education, 2023)
The development of students' potential and achievement in schools is strongly supported by learning practices based on a quality academic culture. This article describes the challenges and efforts of three private religious high schools in the City of East Jakarta to build their academic culture in their respective schools. This study uses qualitative methods, data collection is done through observation, in-depth interviews, focus group discussions (FGD) and secondary data collection. The subjects in this study were school principals, teachers, students and parents in three senior high schools which became the locus of this study. The results of this study indicate that the challenges and efforts to develop an academic culture are responded to differently. Each school that is our research focus mobilizes its resources to build and develop an academic culture. Challenges and efforts to develop an academic culture are of course related to school characteristics such as the quality of human resources, infrastructure and financial capabilities owned by each school itself.